English for Children 5-7 Years Old - Nematovna, Ergasheva Gulnora (Researchparks Publishing, 2023)
The following article describes the main benefits of learning a second foreign language in preschool age. Knowledge of foreign languages broadens one's horizons and makes one feel at home anywhere in the world. And what parent does not want their child to have a developed intellect and open doors everywhere? Therefore, more and more children are taught foreign languages from a very young age. It is believed that children are much easier to get used to a foreign culture than an adult. But English for children requires a special teaching methodology, which we will talk about today. We will tell you how to instill in your child an interest in learning and advise on ways in which you can conduct English lessons for children easily and effectively.